Coexistence of Stump Appendicitis and Ovarian Fibro-Thecoma in a Young Women with Recurrent Right Iliac Fossa Pain During Pregnancy; A Rare Case Report - Ansari, Sana (Med Phoenix, 2021)
Ovarian Fibro-thecoma is a rare, benign, sex cord-stromal neoplasm, with a typically unilateral location in the ovary, characterized by mixed features of both fibroma and thecoma. Ovarian Fibro-thecoma is Uncommon tumor of gonadal stromal cell origin accounting for 3-4% of all ovarian tumors. We describe a rare case of Fibro-thecoma in a 27- year women with a history of recurrent right iliac fossa pain during pregnancy associated with fever and vomiting with previous history of laparotomy for appendicular abscess 10 years back. She presented to us during pregnancy with this complain for which she was managed conservatively. She did not maintain her follow up regularly at our hospital and visited again after delivery of her baby with a still birth outcome with a newly diagnosed complex bilateral ovarian cyst demonstrated on ultrasound and computed tomography showed inflammatory Right sided tubo-ovarian mass along with inflammatory thickening of ileum in right lower quadrant adjacent to right ovarian mass lesion. The patient underwent laparotomy for this with the removal of mass along with the removal of appendicular stump for appendicular stump appendicitis which was diagnosed intraoperatively. The finding from histopathological examination of the mass was consistent with the diagnosis of Fibro-thecoma.